2023
DOI: 10.3390/children10020291
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Protective Behaviors of Teachers on Skin Cancer: A Cross-Sectional Survey Study from Turkey

Abstract: Background: People socialize and receive education and training for the first time outside the home at school, where their teachers act as role models. Teachers play a crucial role in instilling sun-protection habits in children. Avoiding the sun between 10 a.m. and 4 p.m., staying in the shade, wearing sun-protective clothing, wearing sunglasses, wearing hats, using sunscreen products, and using an umbrella are some of the sun-protection methods described in the literature. This study sought to assess teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Cancer experiences of relatives is also significantly related to awareness of cancer risk factors and cancer warning signs. This result may be supported by the findings of previous studies, which showed that those with a family history of cancer have a higher awareness of cancer risk factors than those without [ 41 ]; they also have a higher level of cancer knowledge [ 28 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Cancer experiences of relatives is also significantly related to awareness of cancer risk factors and cancer warning signs. This result may be supported by the findings of previous studies, which showed that those with a family history of cancer have a higher awareness of cancer risk factors than those without [ 41 ]; they also have a higher level of cancer knowledge [ 28 ].…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown that male secondary school teachers in Malaysia had very poor knowledge of risk factors related to lung cancer [ 26 ], female high school teachers in Saudi Arabia had inadequate knowledge of risk factors and prevention of cervical cancer [ 27 ], and about half of primary through high school teachers in Turkey had knowledge of the risk factors and signs of skin cancer [ 28 ]. Thus, it was noted that school teachers’ knowledge and awareness of cancer is inadequate in other countries, and the results were similar in Japan.…”
Section: Discussionmentioning
confidence: 99%